Mechanical Properties of Compressed Wood with Various Compression Ratios - Buan Anshari; Akihisa Kitamori; Kiho Jung; Kohei Komatsu; Zhongwei Guan (Masyarakat Peneliti Kayu Indonesia, 2016)
This paper investigates five groups of compressed wood (CF), four of them made from compressed Japanese cedar with four different compression ratios (CR) of 33%, 50%, 67% and 70% and one without compression (control). The specimens were conditioned in relative humidity (RH) of 60% with moisture content (MC) of 12%. Mechanical properties tested were shear modulus in LR, LT and RT planes by single cube test method, Young’s modulus in the L, R, T directions and poisson’s ratios in all planes. Results showed that in comparison with control specimen, the average improvement on density with CR improvement were 25%, 75%, 175% and 261% corresponding to CRs of 33%, 50%, 67% and 70% respectively. It was also found that Young’s modulus in the L and T directions increased significantly with the increase of CR. Shear modulus of RT plane increased with the rise of CR. Poisson’s ratios tended to decrease with increasing compression ratio of CW.